Electronic, magnetic and spectroscopic properties of doped Mn(1−x)AxWO4 (A = Co, Cu, Ni and Fe) multiferroic: an experimental and DFT study. (29th December 2016) - Mal, Priyanath; Bera, G; Rambabu, P; Turpu, G R; Chakraborty, Brahmananda; Ramaniah, Lavanya M; Singh, R P; Sen, Pintu; Das, Pradip
Abstract: The influence of dopants (Co, Cu, Fe and Ni) on the optical, electronic and magnetic properties of multiferroic MnWO4 was studied using Raman spectroscopy, ultraviolet–visible spectroscopy (UV–Vis), magnetization measurements and density functional theory (DFT) calculations. The evolution of Raman spectra with different elemental substitutions at the Mn site was also studied, where the peak width increased with doping of higher mass elements (Co, Cu, Fe and Ni). UV–Vis diffuse reflectance spectroscopy on polycrystalline Mn(1− x ) A x WO4 ( A = Co, Cu, Fe and Ni) (0 ⩽ x ⩽ 0. was performed. The evaluated electronic band gap decreasing with successive Co, Cu and Fe doping reflected the lower ionic radius of the substituted element, and for Ni-doped MnWO4 the band gap increased slightly compared to the parent MnWO4 . Bader charge transfer and a partial density of states (PDOS) analysis from DFT simulations predict the appearance of impurity states in the band gap region (of pure MnWO4 ) from the d orbital of the dopant (Co, Cu and Fe) hybridized with the p orbital of the bonded O atoms due to charge transfer from O to the dopant, and reduced the band gap of Co, Cu and Fe-doped MnWO4 . On the other hand, for Ni-doped MnWO4 strong W–O hybridization occurring due to large charge transfer from oxygen to tungsten leads to an increase in the band gap. The band gap, computed using the GGA + U method, is close to the experimental value. The signature of the d–d transition observed in the UV spectra is explained in terms of the crystal field stabilization energy caused by the octahedral distortion present in the lattice. Three different antiferromagnetic phases (AF1, AF2 and AF3) are identified in MnWO4 and also for the Co (18.75%)-doped sample. For Cu-doped samples, suppression of the AF1 phase and stabilization of the AF2 phase is observed up to 2 K. Successive doping of Cu leads to the diminution of magnetic frustration. A new magnetic order is identified for Ni-doped MnWO4 in the temperature range 13.7–20 K.